Риск формирования «дисфункциональных сдвигов» у беременных женщин при дефиците нутриентов в рационе питания - Супрун, С.В.; Евсеева, Г.П.; Козлов, В.К.; Морозова, О.Н.; Целых, Е.Д. (Таврический медико-биологический вестник, 2013)
Проведено дослідження добового раціону харчування вагітних жінок Приамур’я (на прикладі м.
Хабаровська). Виявлено часткову субстратно-енергетичну недостатність. Визначено дефіцит основних
нутрієнтів (білків, жирів, вуглеводів). Середній вміст білка в продуктах добового фактичного індивідуального
раціону харчування вагітних жінок був нижче регламентованої потреби для даного регіону в 2,1 рази,
жирів – в 1,3 рази, вуглеводів – в 2 рази. Виявлено різке порушення співвідношення нутрієнтів (білки: жири:
вуглеводи) у 77,3-90,9% вагітних. Аналіз інтегральних показників функціонального відгуку організму показав
їх відповідність регіональним нормативам у 18,2% вагітних; межі «формування специфічних адаптивних
якостей» – у 13,6% жінок. Більшість вагітних (54,5%) склали групу «функціонального напруження організму»;
13,6% спостережуваних жінок схильні до високого ризику «дисфункціональних зрушень». We have researched the daily diet of pregnant women who are residents of Khabarovsk, the Preamurye Region,
which shows a certain substrate-energy deficiency. A shortage of basic nutrients (proteins, fats, carbohydrates)
has been revealed. Against the official food-product demand values in this region, the average protein content in
the individual daily diets of pregnant women is 2,1 times lower and the average daily fat is 1,3 times lower, the
carbohydrate content is 2 times lower. Severe misbalances of nutrients – protein, fat, and carbohydrates have been
found in 77,3-90,9% of pregnant women. An analysis of the data obtained has shown that the integral indices of
the organism response (IIOR) conform to the regional norms in 18,2% of pregnant women. The level of IIOR was
adequate to the limit for the «formation of specific adoptive features» in 13,6% of cases. The majority of pregnant
women (54,5%) compose the group of «the functional distress of organism»; 13,6% of pregnant women are at a
high risk of development of dysfunctional changes.